Epidemiology and significance of surgical margins in the management of HPV-associated vulvar precancers (H-SIL) - analysis of own data - Pichlík, Tomáš; Rob, Lukáš; Halaška, Michael J.; Drozenová, Jana; Robová, Helena (Ceska gynekologie, 2022)
OBJECTIVE: Epidemiology and evaluation of the importance of surgical margins in the treatment of vulvar H-SIL - analysis of own data. MATERIAL AND METHODS: The prospective study included women dia-gnosed with HPV-associated vulvar epithelial neoplasia from 10/2016 to 1/2022. A total of 65 women were included. After surgical treatment, the women were distributed to groups according to surgical margins and were followed-up at regular intervals. RESULTS: Seventeen women (26%) dia-gnosed with HPV-associated vulvar intraepithelial neoplasia were under 49 years, whereas 48 women (74%) were older than 49 years. Recurrence rates of HPV-associated precancers were 12.3%, 1.5% and 3.1% in excisions with positive margins up to 1mm peripheral margins and 1-3mm peripheral margins, respectively. The risk of recurrence when the lesion reaches the margin is statistically significant, compared to a healthy margin of 1-3mm. CONCLUSION: Keeping the minimal healthy margin (1-3mm) seems to be an acceptable risk of recurrence of HPV-associated vulvar intraepithelial neoplasia with positive cosmetic effect and minimal risk of disturbing the psychosexual functions of women. Long-term regular follow-up is necessary.
Keywords: Female; Papillomavirus Infections; H-SIL; resekční okraje; ženské pohlaví; Papillomaviridae; vulvar intraepithelial neoplasia; lidé; nádory vulvy; Vulva; Carcinoma in Situ; Vulvar Neoplasms; Epidemiology; type 1 diabetes; prospektivní studie; Prospective Studies; infekce papilomavirem; Margins of Excision; surgical margins; vulva; karcinom in situ; Humans